2018
DOI: 10.1007/s00426-018-1014-7
|View full text |Cite
|
Sign up to set email alerts
|

Judgements about double-embedded relative clauses differ between languages

Abstract: When the middle verb phrase is removed from an English double-embedded sentence, the remainder of the sentence is read faster in spite of the ungrammaticality. It has been shown that this "missing-VP effect" is reversed in German and Dutch. The current study demonstrates that the same cross-linguistic difference holds for sentences judgments: Native speakers consider English double-embedded sentences more comprehensible and acceptable when the middle verb phrase is removed, whereas the same is not the case in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 29 publications
3
30
1
Order By: Relevance
“…In addition, various corpus analyses (Futrell et al, 2015; Liu, 2008; Rajakrishnan et al, 2016; Temperley, 2007) also provide evidence for the dependency minimization hypothesis, which is based on the assumption of limited working memory capacity. Our results lend support to a large body of work in the processing literature that highlights the importance of linguistic exposure and its interaction with working memory constraints in determining processing complexity in various languages (Boston et al, 2008; Demberg & Keller, 2008; Frank & Ernst, 2019; Husain et al, 2014, 2015; Levy, 2013; Levy et al, 2013; Levy & Keller, 2013; Staub, 2010; Vasishth & Drenhaus, 2011). Similar importance to linguistic exposure and its effect on processing is given by the connectionist models of processing (Christiansen & Chater, 1999; Christiansen & MacDonald, 2009; Engelmann & Vasishth, 2009; Frank et al, 2016; MacDonald & Christiansen, 2002).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In addition, various corpus analyses (Futrell et al, 2015; Liu, 2008; Rajakrishnan et al, 2016; Temperley, 2007) also provide evidence for the dependency minimization hypothesis, which is based on the assumption of limited working memory capacity. Our results lend support to a large body of work in the processing literature that highlights the importance of linguistic exposure and its interaction with working memory constraints in determining processing complexity in various languages (Boston et al, 2008; Demberg & Keller, 2008; Frank & Ernst, 2019; Husain et al, 2014, 2015; Levy, 2013; Levy et al, 2013; Levy & Keller, 2013; Staub, 2010; Vasishth & Drenhaus, 2011). Similar importance to linguistic exposure and its effect on processing is given by the connectionist models of processing (Christiansen & Chater, 1999; Christiansen & MacDonald, 2009; Engelmann & Vasishth, 2009; Frank et al, 2016; MacDonald & Christiansen, 2002).…”
Section: Discussionsupporting
confidence: 78%
“…In particular, it has been claimed that head‐final languages (e.g., German, Hindi, Japanese) allow for longer head‐dependent distance. Previous work on predictive processing (Husain et al, 2014; Konieczny, 2000; Levy & Keller, 2013; Miyamoto & Nakamura, 2003; Nakatani & Gibson, 2010; Vasishth & Lewis, 2006) as well as the forgetting effect (Frank & Ernst, 2019; Frank et al, 2016; Husain & Bhatia, 2018; Vasishth et al, 2010) shows that head‐final languages allow for longer distance in dependencies involving verbal heads (but see Safavi, Husain, & Vasishth, 2016; Vasishth & Drenhaus, 2011). For example, with regard to the forgetting effect, it has been shown that contrary to the results in an SVO language like English, in SOV languages like German, Dutch, and Hindi, increased HD (in the form of embedding) does not lead to forgetting of the upcoming verbs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…German materials are shown in the sentences (4); these are word‐for‐word translations of the English materials in (3). Vasishth et al () probed the structural forgetting effect using reading times for material after the end of the verb phrases, and Frank and Ernst () have replicated the effect using acceptability judgments (but see Bader, ; Häussler & Bader, , for complicating evidence).…”
Section: Structural Forgettingmentioning
confidence: 99%